Desarrollo de la competencia de lectura inferencial en jóvenes y adultos - Reyes, Nathalie (Universidad de San Buenaventura, Cali, 2018)
The present degree work contains a process of educational research applied to the classroom realized with the objective of contributing to the development of the inferential reading competence of the students of the Formal Education Program for youth and adults of the CLEI III of the Educational Institution Álvaro Echeverry Perea of Santiago de Cali (V) through a didactic sequence based on myths and legends, given that in the Pedagogical Practice I (2016-2) and II (2017-1) of the Degree in Spanish Language some difficulties of this population were found, the difficulties were to elaborate assumptions from the data extracted from the texts. To achieve this objective, a descriptive, qualitative, and research process was realized since it was required to recognize and determine the properties of the object of study through the bibliographic approach and in the school field to characterize them; the process was carried out in methodological moments that allowed to triangulate the theoretical, the experiential and the obtained results; the derived analysis made possible the proposal of a didactic sequence designed in coherence with the learning characteristics of the young people and the adults.